Accuracy and Precision in Acupuncture Point Location: A Critical Systematic Review - Debra R. Godson; Jonathan L. Wardle (Medical Association of Pharmacopuncture Institute, 2019)
A number of studies have examined the accuracy and precision of acupuncture point location across various point location methods. Accuracy of point location is essential for safe, efficacious and reliable treatments and valid reproducible research outcomes. This review aims to identify, summarize, compare and critically appraise available empirical studies relating to the accuracy and precision of acupuncture point location. A comprehensive search of five electronic databases, World Journal of Traditional Chinese Medicine and Google scholar was performed for studies investigating accuracy and precision in acupuncture point location. 771 studies were screened of which 14 studies were identified, including 9 studies that investigated the localization of acupoints and 5 studies that examined the cun measurement system. Considerable variation in localization of acupoints was reported among qualified medical acupuncturists. Variation in point location among qualified non-medical acupuncturists is unknown due to lack of any identified study. The directional method was found to be significantly inaccurate and imprecise in all studies that evaluated the method. Suitability of other methods for clinical and research purposes and influencing factors such as education, training and experience were identified as topics for future studies. Keywords: Acupoint, Acupuncture, Acupuncture point, Point location, Professional competence